Complement Activation in Nephrotic Glomerular Diseases - Dominik Nell; Robert Wolf; Przemyslaw Marek Podgorny; Tobias Kuschnereit; Rieke Kuschnereit; Thomas Dabers; Sylvia Stracke; Tilman Schmidt (Biomedicines, 2024)
The nephrotic syndrome holds significant clinical importance and is characterized by a substantial protein loss in the urine. Damage to the glomerular basement membrane or podocytes frequently underlies renal protein loss. There is an increasing belief in the involvement of the complement system, a part of the innate immune system, in these conditions. Understanding the interactions between the complement system and glomerular structures continually evolves, challenging the traditional view of the blood–urine barrier as a passive filter. Clinical studies suggest that a precise inhibition of the complement system at various points may soon become feasible. However, a thorough understanding of current knowledge is imperative for planning future therapies in nephrotic glomerular diseases such as membranous glomerulopathy, membranoproliferative glomerulonephritis, lupus nephritis, focal segmental glomerulosclerosis, and minimal change disease. This review provides an overview of the complement system, its interactions with glomerular structures, and insights into specific glomerular diseases exhibiting a nephrotic course. Additionally, we explore new diagnostic tools and future therapeutic approaches.